The Effect of Propolis Addition on the Quality of Marshmallows in Terms of Texture, Water Content, Water Activity (Aw), and Color - Kurniati, Fatma; Amertaningtyas, Dedes (Faculty of Animal Science Universitas Brawijaya, 2025)
Marshmallow is a type of soft candy that is popular with consumers, including confectionary products made from gelatin, sugar and sweeteners. Innovations in making marshmallows were carried out with the addition of propolis to increase the functional value of food so that it has a positive impact on health. The purpose of this research is to determine the effect of propolis addition on the texture, water content, water activity (Aw), and color (L, a*, b*). The materials used in this research included propolis, gelatin, sugar, water, and cornstarch. The research method applied was experimental research using a Completely Randomized Design (CRD) with four treatments and five replications consisting P0 (0% propolis), P1 (3% propolis), P2 (5% propolis), and P3 (7% propolis). The observed variables were texture, water content, Aw, and color (L, a*, b*). The obtained data were analyzed using Analysis of Variance (ANOVA), and if significant differences were found, further analysis was conducted using Duncan’s Multiple Range Test (DMRT). The results of the research on marshmallows with the addition of propolis showed mean values for texture (0.56 N-0.92 N), moisture content (26.21%-34.26%), Aw (0.804-0.811), lightness (L) (92.90-93.58), redness (a*) (0.060-0.212), and yellowness (b*) (24.826-25.542). The conclusion of this research is the addition of propolis to marshmallows significantly affected texture and water content but had no effect on Aw and color (L, a*, b*) values. The best treatment was P1, with 3% propolis addition, resulting in a texture of 0.920 N ± 0.268, water content of 31.408% ± 0.571, Aw of 0.804 ± 0.003, L value of 93.132 ± 0.769, a* value of 0.196 ± 0.092, and b* value of 25.542 ± 0.559. These results indicate that the addition of 3% propolis can improve texture and maintain balanced moisture content without altering the stability of water activity and color. Based on the results of this study, it is recommended to use 3% propolis in marshmallow production, as it yields the best quality in terms of texture, moisture content, Aw, and color (L, a*, b*).